Kepastian Hukum dalam Kebijakan Penetapan Nilai Transaksi sebagai Dasar Pengenaan Bea Perolehan Hak Atas Tanah dan Bangunan (BPHTB) di Kabupaten Karanganyar - Aufa Rida Fortuna (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2026)
Law of The Republic Indonesia concerning Local Taxes and Retribution mentioned that Acquisition Duty of Right on Land and Building (BPHTB) basis over the transaction is using the transaction value. The BPHTB collection in Karanganyar regency is based on The Local Regulation Number 14 the Year 2010 concerning BPHTB. However, the mechanism of determining the transaction value has not been concretely regulated in the Rule of Laws or KTUN. This research aims to analyze the legal certainty in determination policy of transaction value as the BPHTB basis in Karanganyar regency and what kind of legal implications will arise in the determination policy of transaction value as BPHTB basis in Karanganyar region, which is contrary to the legal certainty. The method of normative legal research, with the typical characteristics of perspective by using primary and secondary legal materials which analyzed by deductive logic reasoning method is being used to conduct this research. The legal material collection technique used is literature study and in-depth interviews that being done with the Local Government Finance Office and Land Deed Official (PPAT).